6x²+x-12
the first thing we need to do is find 2 numbers that add up to equal the middle term (1) but multiply together to get a product of -72 (-12*6)
two numbers that would fit this is 9 and -8
so now we placed 9x and -8x in place of the middle term
6x²+9x-8x-12
now we look for whats common between the first two numbers and divide them out
6x²+9x = 3x(2x+3)
now we do the same with the last two numbers
-8x-12 = -4(2x+3)
notice how the numbers in brackets are the same (2x+3)
we will keep (2x+3) and then combine the numbers on the outside
once we do that you should get an answer of
(3x-4)(2x+3)
hope this helped!
Answer:
15.83 ounces
Step-by-step explanation:
95/6 is about 15.83
Use division to divide things evenly
Bruh............................
1,132 people came to watch the balloon festival.
(X)+2(x+1)=26
3x=24
X=8
Y=x+1
Y=8+1
Y=9
The two numbers are 8 and 9